Stem Cells for Spinal Cord Injury – Are we Closer to Clinical Application in Humans? - Saqib Kamran Bakhshi; Rashid Jooma (Journal of the Pakistan Medical Association, 2023)
Recovery after spinal cord injury (SCI) is highly variable, often leaving the victim disabled for life and having to deal with the complications of paraplegia. Stem cell therapy is a potential hope for these patients. Most of the research on use of stem cells for SCI has been on animal models in laboratories. Some recent clinical trials involving human subjects have shown positive outcomes with regards to tissue growth after transplantation, but meaningful functional recovery is yet to be seen. The emergence of lumbar cord simulation is a new approach and the recent identification of recovery organizing interneurons points to a pathway that could integrate neuromodulation with cellular therapy. Keywords: Spinal Cord, Paraplegia, Stem Cell, Transplantation, Interneurons